Chemical Characterization of Hydrogels Crosslinked with Polyethylene Glycol for Soft Tissue Augmentation - Damiano Monticelli; Virginia Martina; Roberto Mocchi; Raffaele Rauso; Umberto Zerbinati; Giovanna Cipolla; Nicola Zerbinati (2019)
Hyaluronic acid (HA) based hydrogels for esthetic applications found widespread use. HA should be crosslinked for this application to achieve the correct viscoelastic properties and avoid fast degradation by the hyaluronidase enzyme naturally present in the skin: these properties are controlled by the amount of crosslinker and the fraction that is effectively crosslinked (i.e. that binds two HA chains).Crosslinking by polyethylene glycol diglycidyl ether (PEGDE) has been more recently introduced and showed attractive features in terms of viscoelastic properties and reduced biodegradation. Aim of this paper is to define a method for the determination of the crosslinking properties of these recently introduced fillers, method that is lacking at the moment.The percentage of crosslinker and the fraction that is effectively crosslinked were determined by proton Nuclear Magnetic Resonance (1H NMR) and by 13C NMR, respectively. The filler were preliminarily washed with acetonitrile to remove residual PEG and then digested by hyaluronidase to obtain a sample that can be analysed by NMR.The crosslinking parameters were determined in four samples of NEAUVIA PEG-crosslinked dermal fillers (produced by MatexLab S.p.A., Italy). The percentage of crosslinker was between 2.8% and 6.2% of HA, whereas the effective crosslinker ratios were between 0.07 and 0.16 (ratio between the moles of effectively crosslinked PEG and total moles of PEG). Moreover, a digestion procedure alternative to enzymatic digestion, based on acidic hydrolysis, was successfully tested for the determination of crosslinker percentage.The proposed method successfully determined the two crosslinking parameters in PEG-crosslinked dermal fillers. The estimated percentage of crosslinker is similar to previously reported data for other crosslinkers, whereas the effective crosslinker ratio is lower for PEG crosslinked hydrogels.